Arsenite (III) removal via manganese-decoration on cellulose nanocrystal -grafted polyethyleneimine nanocomposite. (September 2022) - Luo, Tingting; Wang, Runkai; Chai, Fei; Jiang, Lei; Rao, Pinhua; Yan, Lili; Hu, Xinjian; Zhang, Wei; Wei, Lianghuan; Khataee, Alireza; Han, Ning
Abstract: The manganese is successfully induced as a "bridge joint" to fabricate a new adsorbent (CNC–Mn-PEI) connecting cellulose nanocrystal (CNC) and polyethyleneimine (PEI) respectively. It was used to remove As (III) from waste water. It has been proved that the incompact CNC and PEI were successfully connected by Mn ions, which induced the formation of O–Mn–O bonds and the removal efficiency is maintained in the broad pH range of 4–8, even with the influence of NO3 − and CO3 2− . The CNC–Mn-PEI was characterized by Brunauer–Emmett–Telley (BET) method and the results showed that the nanoparticle of the specific surface area was 106.5753 m 2 /g, it has a significant improvement, compared with CNC–Mn-DW (0.1918 m 2 /g). The isotherm and kinetic parameters of arsenic removal on CNC–Mn-PEI were well-fitted by the Langmuir and pseudo-second-order models. The maximum adsorption capacities toward As (III) was 78.02 mg/g. After seven regeneration cycles, the removal of As (III) by the adsorbent decreased from 80.78% to 68.2%. Additionally, the hypothetical adsorption mechanism of "bridge joint" effect was established by FTIR and XPS, which provided the three activated sites from CNC–Mn-PEI can improve the arsenic removal efficiency, and providing a new stratagem for the arsenic pollution treatment. Graphical abstract: Image 1 Highlights: The introduction of polyethyleneimine can effectively organize the forces between the molecular chains of manganese-based cellulose materials. The removal efficiency of manganese-based cellulose materials was greatly enhanced with the introduction of polyethyleneimine for arsenite (III) removal. The "bridging effect" of Mn was confirmed by inducing a large amount of the activated sites.